Pengaruh Pendapatan Pembiayaan Ijarah dan Istishna terhadap Laba Bersih pada Bank BJB Syariah - Wita Yulianti; Ade Iskandar Nasution; Bahmid I Magi (Ma'soem University, 2022)
Based on the results of preliminary research, that the background of this research is the fluctuation of Ijarah and Istishna financing income which causes the fluctuation of Net Profit income in BJB Syariah Bank. This study aims to determine how the influence of Ijarah financing income on Net Profit at Bank BJB Syariah, knowing how the influence of Istishna financing income on Net Profit at Bank BJB Syariah, and knowing how the influence of Ijarah and Istishna financing income on Net Profit at Bank BJB Syariah. The object of research in this report is to measure the Net Profit at Bank BJB Syariah. The type of research is associative quantitative, secondary data type and by using data collection techniques in the form of documentation and literature study. As for the sampling technique is non-probabilty sampling, with a population of all financial reports of Bank BJB Syariah with a sample of quarterly financial reports of Bank BJB Syariah for the period 2016-2020. The results of the study show that partially Ijarah financing income has no significant effect on net income at BJB Syariah Bank, with the results of the t test where the value of t count < t table (-1,105 < 1,734), Istishna financing income partially has no significant effect on net income at Bank BJB Syariah with the results of t test where the value of t count < t table (0,458 < 1,734), Ijarah and Istishna financing income simultaneously has no significant effect on net income at Bank BJB Syariah with F test results where the calculated F value < F table (2,894 < 3,59).